Peran Suplementasi Vitamin D dalam Pencegahan Eksaserbasi Asma - Laporan Kasus Berbasis Bukti: Analisis - Sagitania, Devina (Cermin Dunia Kedokteran, 2025)
Background: Asthma is a chronic inflammatory condition affecting the airways, marked by tissue changes and heightened bronchial sensitivity. Vitamin D, as an immunomodulator, may affect the inflammatory responses of the airways. Recent studies suggest that vitamin D supplementation has resulted in fewer exacerbations of asthma and improved lung function in both individuals with asthma and smokers. Other studies revealed a reduction of asthma exacerbations in corticosteroid-treated patients. This study sought to investigate whether vitamin D supplementation can decrease the frequency of asthma exacerbations. Methods: Literature research was done on three databases: PubMed, Cochrane Library, and ScienceDirect, related to the clinical question. Articles were chosen according to specific inclusion and exclusion criteria. All articles were critically appraised using the Oxford Center for Evidence-Based Medicine worksheet. Results: Three meta-analysis articles were critically appraised. The result is vitamin D supplementation can lower the incidence of asthma exacerbation, despite varying doses of vitamin D. Conclusion: Vitamin D supplementation was associated with a decrease in asthma exacerbations, despite varying doses of vitamin D. Vitamin D supplementation to corticosteroids can be considered potentially cost-effective and safe to prevent asthma exacerbations. Future studies should analyze the effect of vitamin D supplementation in long-term asthma therapy using the same dose.